High-voltage switchgear and controlgear. Guidance for the extension of validity of type tests of AC metal and solid-insulation enclosed switchgear and controlgear for rated voltages above 1 kV and up to and including 52 kV Part 307, (17th July 2019) - British Standards Institution,
No abstract available